2013
DOI: 10.1155/2013/263150
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Oral Cancer in a Northwestern Nigerian State: Assessing the Knowledge, Opinion, and Practice of Traditional Healers and Herbalists

Abstract: Background: Traditional healers/herbalists remain one of the most accessible and popular options of care to people suffering from cancers particularly at the community level in Nigeria. The majority of patients with oral cancer present at the terminal stage after exploring unorthodox care. This study assesses the awareness of oral cancer among traditional caregivers in Kano State, Northwestern (NW) Nigeria.Methods: Self-administered, structured questionnaires were administered to a cross section of 21 traditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…In a similar study by Varela-Centelles et al, only 2.6% of herbalists suggested the correct referral system and 86.4% recommended OTC remedies instead. (2) Also the results of the study by Adebola et al showed that only 33.3% of herbalists were informed of oral cancer in Nigeria, (1) while higher levels of awareness were reported in the United State (56%). Nearly 10% of the pharmacies surveyed in this study recommended OTC drugs only and 11% prescribed medications in combination with referral to a medical or dental practitioner for consultation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a similar study by Varela-Centelles et al, only 2.6% of herbalists suggested the correct referral system and 86.4% recommended OTC remedies instead. (2) Also the results of the study by Adebola et al showed that only 33.3% of herbalists were informed of oral cancer in Nigeria, (1) while higher levels of awareness were reported in the United State (56%). Nearly 10% of the pharmacies surveyed in this study recommended OTC drugs only and 11% prescribed medications in combination with referral to a medical or dental practitioner for consultation.…”
Section: Discussionmentioning
confidence: 99%
“…(1,2) The risk of oral cancer is higher in those aged more than 65 years, black males and chronic alcohol and tobacco users. (1) World Health Organization (WHO) has reported oral cancer as the sixth most common cancer in males after lung, prostrate, colorectal, stomach, and bladder cancer while in females it is the tenth most common cancer after breast, colorectal, lung, stomach, uterus, cervix, ovary, bladder, and liver cancer. (3) The worldwide rate of oral cancer is lower than breast, prostate, and colon cancers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 2 cases reported by Ajagbe presented at 6 months and the case reported by Williams presented at 8 months. It is an indicator of poor attitudes towards healthcare in Nigeria and most developing countries [ 13 ]. By her admission, the mother was only motivated to seek care when feeding was affected and cosmetic compromise was marked.…”
Section: Discussionmentioning
confidence: 99%